(untitled) (Agricultural Engineering, 2022)
Peanut is an important produce in the global food chain because of their high-quality oil and protein content. Due to the significant value of its production in Iran, a threshing machine was developed for high-quality harvesting, to reduce harvesting costs and labor effort. In the course of a number of field experiments to evaluate the performance of the machine, the rotational speed of the thresher was adopted at three levels of 150, 200, and 300 rpm. Other experimental factors included the distance of the concave from the thresher (2, 6, and 8 cm) and the product feeding rate of 750, 850, and 950 kg·h−1. Regarding the measurements, the threshing efficiency, the separation rate, and the percentage of the crushed product were calculated and evaluated. The results revealed that as the rotational speed of the thresher, the increment feeding rate of the product and the distance between the thresher and the concave grate increased, the thresher efficiency decreased. The maximum threshing efficiency of 95% was obtained at a rotational speed of 150 rpm and a distance of 2 cm. Also, with increasing the rotational speed of 300 rpm and a distance of 8 cm, the threshing efficiency decreased to 75%. The separation rate decreased intensely as the distance between the thresher and the concave increased. In addition, the separation rate decreases with increasing rotational speed of the thresher. At a rotational speed of 150 rpm and a distance of 2 cm, the separation rate was 96%, but the separation rate decreased to 76% as rotational speed increased to 300 rpm and distance increased to 8 cm. With increasing rotational speed and feeding rate, the percentage of crushed pods increased. The maximum of 16% was obtained at a rotational speed of 300 rpm, a feeding rate of 950 kg·h−1 and a distance of 2 cm.